Cost-effectiveness of CT, EUS and PET/CT in evaluating patients with symptoms of pancreatic cancer in Colombia (2010)
Abstract Introduction: An estimated 1,399 new cases of pancreatic cancer (PC) and 1,406 deaths from the same cause occurred in Colombia in 2002. We evaluate the cost-effectiveness of multidetector computed tomography (CT), endoscopic ultrasonography (EUS) and positron emission tomography with computed tomography (PET/CT) in diagnosis and staging of patients with clinical suspicion of PC. Materials and methods: We conducted a cost-effectiveness analysis based upon a systematic search to determine the strategies’ sensitivity and specificity. The costs of administering and monitoring were taken from the official tariff manuals. The results were assessed in terms of number of correct behaviours. We performed deterministic and probabilistic sensitivity analyses. Results: CT showed the best cost-effectiveness indicator (Col$ 3,397,163 for each appropriate behaviour). The cost of changing the strategy to that of CT plus EUS was Col$ 7,893,573 for each additional appropriate behavior. In the probabilistic analysis the cost-effective strategy was USE for a willingness to pay higher than Col$ 9,000,000 per additional unit, or TAC for smaller values. Conclusion: The cost-effective strategy in the evaluation of patients suspected PCis the multidetector CT. For values of willingness to pay more than Col$ 7,893,573 and Col$ 9,000,000 per additional unit cost-effective alternatives are EUS or CT plus EUS in series.